Caring attributes, professional self concept and technological influences in a sample of Registered Nurses in eleven countries - Arthur, D; Pang, S; Wong, T; Alexander, M.F; Drury, J; Eastwood, H; Johansson, I; Jooste, K; Naude, M; Noh, C.H; O'Brien, A; Sohng, K.Y; et al. (International journal of nursing studies, 1999)
Caring, the theoretical foundation of nursing, is identified as one of the core values by Hospital Authorities world-wide to be actualised in clinical practice. Exactly how caring attributes relate to nurses' professional self image and quality nursing service in the context of a contemporary technological environment have yet to be operationalised. In total, 1957 Registered Nurses from 11 different countries were involved in the study which aimed to: develop an understanding of and compare the responses to items relating to caring, professional self concept and technological influences. To collect data an instrument containing 104 Likert items was administered to RNs working in general hospitals. The instrument contained sections which examined professional self concept, technological influences and caring attributes. Descriptive and inferential statistics revealed that many of the Asian nurses in the sample were younger, had less experience yet were more qualified than their ‘western’ colleagues. The mean scores for the caring attributes for nurses from the Philippines, Sweden and South Africa were significantly higher than those from China (Beijing), Korea, China (Hong Kong) and Scotland. The Korean sample demonstrated the lowest mean score for professional self concept while the New Zealand sample the highest. The Australian, Canadian, NZ, Scotland and Swedish samples were strongly of the opinion that the increase in technology has not brought about the any more spare time in nursing and generally had a more negative opinion about the influence of technology when compared to those from China (Beijing), Philippines, China (Hong Kong) and Singapore. The results are discussed in the light of the cultural differences in the sample and recommendations for future research are considered.